Third Parties’ Legal Protection over Agreed Authorized Capital Amount by Founders in Limited Liability Companies - Nugraha, Xavier; Murti, Krisna; Putri, Saraswati (Lentera Hukum, 2019)
On July 14, 2016, the Government enacted the Government Regulation Number 29 of 2016 regarding Amendments in Authorized Capital of a Limited Liability Company (LLC). Article 1 paragraph (3) of the regulation showed that the amount of authorized capital was submitted to the agreement of the LLC founders. This regulation was issued in order to increase Indonesia’s ‘ease of doing business’ rank, especially in ‘starting a business.’ This article aims to examine the legal protection for the third party over the amount of authorized capital based on the agreement of the LLC founders using the study of dogmatic law. Regulations referenced are Law Number 40 of 2007 regarding Limited Liability Companies and Government Regulation Number 29 of 2016 regarding Amendments in Authorized Capital of LLC. Based on the results of this study, it was found that the determination of authorized capital based on the agreement of LLC founders has neglected the protection of the third parties. This manifested particularly in protecting minority investors and resolving insolvency. Through the enactment of authorized capital based on the agreement of the founders, the mechanism of preventive and repressive legal protection to the third parties are assumed to be eliminated. Keywords: The Authorized Capital, Limited Liability Company, Agreement, Legal Protection.